Intestinal Claudin-7 deficiency impacts the intestinal microbiota in mice with colitis - Yuhan Ding; Kun Wang; Chang Xu; Mengdi Hao; Huimin Li; Lei Ding (BMC Gastroenterology, 2022)
Abstract Background Intestinal epithelial cells form a physical barrier that protects the intestine against the intestinal microbiota through tight junctions (TJs) and adhesive junctions, while barrier disruption may lead to inflammatory bowel disease (IBD). Claudin-7 (Cldn7) has been implicated in this protection as an important member of TJs. Here, we experimentally study the effect of Cldn7 deletion on intestinal microbiota in colitis. Methods Colitis model was established based on inducible intestinal conditional Cldn7 gene knockout mice (Cldn7fl/fl; villin-CreERT2), by feeding with dextran sodium sulfate (DSS). AB-PAS staining and immunohistochemical staining of Muc2 mucin were used to detect the effect of Cldn7 deficiency on the mucus layer of mice with colitis, and fluorescence in situ hybridization was used to detect how Cldn7 promotes spatial separation of the gut microbiota from the host. The microbiota population was characterized by high-throughput 16S rRNA gene sequencing of DNA extracted from fecal samples. Results Compared with the controls, Cldn7 knockout increased susceptibility to colitis, including greater degree of weight loss, colon shortening, and a significantly higher disease activity index score. DSS-treated Cldn7 knockout mice promoted the migration of bacteria to the intestinal epithelium to some extent by damaging the intestinal mucus layer. Sequencing of 16S rRNA showed that DSS-treated Cldn7 knockout mice reduced the gut microbiota diversity and had greater relative abundance of Escherichia coli. LEfSe analysis indicated that Escherichia coli may be the key bacteria in Cldn7 knockout mice during DSS-induced colitis. Furthermore, the Tax4Fun analysis predicted that DSS-treated Cldn7 knockout mice enriched for microbiota impacting infectious diseases, immune system and metabolic functions. Conclusions Our data suggests an association between intestinal Cldn7 knockout and microbiota dysbiosis during inflammatory events.